Agama Dalam Konteks Bernegara Berdasarkan Pancasila - citranu, citranu citranu (Dharma Duta, 2019)
Religion in the state is made as a foundation the state, the life in state is inseparable from the value of God which is realized in the doctrines of religion. Pancasila as the philosophy of the Indonesian people has an important role in protective the unity and integrity of the nation. The degenerate in the understanding of Pancasila in Indonesia led to the rise of radicalism that could oppose the integrity of the Indonesian Republic, that it was worthy of being understood and the practice of Pancasila was revived. The people must understand the goals and ideas of the state regarding the concept of nationalism and the insight of Indonesian nationality, the practice religion in the state and used the principle of God through religious doctrines in the relations of Pancasila and The Constitution of the Republic of Indonesia of 1945